PENGARUH PENYULUHAN KESEHATAN TENTANG SADARI TERHADAP PENGETAHUAN DAN SIKAP MAHASISWA DALAM UPAYA DETEKSI DINI KANKER PAYUDARA DI PROGRAM STUDI KEBIDANAN PEMATANGSIANTAR - Juliani Purba (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2018)
According to WHO (Word Health Organization) in 2010 and the International Cancer Control union women will develop breast cancer 8-9%. Every year more than 250,000 new cases of breast cancer diagnosed in Europe and approximately 175.00 cases in the United States. This study was conducted to determine the effect of the BSE health education on knowledge and attitude of students in early detection of breast cancer do Pematangsiantar Midwifery Studies Program. The design of this study using Quasi experiment (Experiment ev) with a sample of 66 respondents. The results showed that there is influence of health education with lecture demonstrations and exercise plus (CPDL) of the knowledge of students in the early detection of breast cancer (p = 0.000; Z = -5024) and there is the effect of health education with lecture plus demonstration and training ( CPDL) the attitudes of students in the early detection of breast cancer (p = 0.000; Z = -4.946). For Midwifery Studies Program Pematangsiatar in using CPDL that improved knowledge and attitudes about early detection of breast cancer.